2013
DOI: 10.4025/actascitechnol.v35i2.10286
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of convective drying kinetics of yellow passion fruit bagasse

Abstract: ABSTRACT.This study aimed to analyze the convective drying in fixed bed of yellow passion fruit bagasse. Firstly, the initial moisture of the bagasse was determined in stove, at 105 ± 3ºC for 24 hours. In the drying tests, it was collected the bagasse mass values over time, by using a convective dryer, operated at four temperatures (35, 45, 55 and 65ºC) and three air flow speeds at 0.8, 1.0 and 1.3 m s -1. Having the curves of the drying and of drying rates, it was observed that the temperature had a great in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…The equation giving the highest R 2 and the smallest χ 2 and RMSE value was considered to be the best fitted equation (Menezes et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The equation giving the highest R 2 and the smallest χ 2 and RMSE value was considered to be the best fitted equation (Menezes et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For passion fruit bagasse, Menezes et. al [8] reported that higher migration of water is obtained at higher drying temperature. Alaskali and Satimehin [9] stated that the isosteric heat of adsoption of powders of ginger decreased with increased moisture content.…”
Section: Resultsmentioning
confidence: 98%
“…Nesta situação, verifica-se que a cinética de secagem do yacon não demonstra período de taxa constante, devido a difusão se tornar o mecanismo físico dominante que rege o movimento da umidade na amostra, e, por isso, não ocorre período de taxa constante na secagem de alimentos, como observado por Menezes et al (2013b).…”
Section: Resultsunclassified